The Association of Economic Growth, Foreign Aid, Foreign Direct Investment and Gross Capital Formation in Indonesia: Evidence from the Toda–Yamamoto Approach - Rosdiana Sijabat (Economies, 2022)
This study examines the direction of causality between Gross Domestic Product, foreign aid, foreign direct investment, and gross capital formation in Indonesia from 1970 to 2019, using the augmented Toda–Yamamoto approach with the Granger causality test. Furthermore, this study achieved the unit root test for both variables using the ADF test, which confirmed that the variables studied were cointegrated and had a prolonged equilibrium relationship with GDP, ODA, FDI, and GCA. The Toda–Yamamoto causality test was used to investigate the direction of causality between variables. The results showed a positive one-way causality between ODA and GDP as well as between FDI and GDP. ODA has promoted the expansion of economic and development activities, thereby leading to GDP in Indonesia. However, despite having a long-run relationship, the study failed to prove a causal relationship between ODA and GCA in Indonesia. Therefore, there is a need for more optimal foreign aid management to attract foreign direct investment.